KOMUNIKASI SILANG BUDAYA DAN PENTERJEMAHAN: ANALISIS TEKS TERJEMAHAN KREATIF - Abdul Wahid, Puteri Roslina; Bukhari, Nur Azimah; Minsung, Cho (JURNAL MELAYU SEDUNIA, 2019)
This paper will discuss the elements of cross-cultural communication and translation with a focus on translation strategies used in creative text translation. The translation is very important in understanding the role and influence of culture in everyday life. Globalization opens the door to cross-cultural communication for those interested in interacting in different languages and cultures. When people of different languages communicate, they need the same language to understand each other. The translation is a reasonable way to communicate in such situations. Translation from the point of view of many theorists and practitioners is actually "cross-cultural transfer", "cross-cultural communication" or "cross-cultural events". Translation, therefore, is said to be a bridge that connects communities who speak languages and practice different cultures. Furthermore, translation of various forms of reading material is increasingly being practiced throughout the world. The article describes translation as cross-cultural communication and analyzes the translation of cross-cultural communication elements in creative texts. The research is based on qualitative descriptions. This paper aims to identify and analyze strategies used to translate cultural elements in cross-cultural communication, namely foreignization and domestication. The analysis also shows that there are interdependencies of translation and culture that can explain translation as a means of cross-cultural communication. This has led to the important role of translation in generalization and in particular the understanding of cross-cultural communication.